A identificação como efeito do processo tradutivo da sedução originária. - Paula, Marina Pinto de (2011)
This study aimed to carry out a proposal for the concept of identification for the Generalized Theory trough Freud's work examination. With a careful identification of the bailout proposed by Freud, we assume that the element common to all identification, not only hysterical, it's sexual, an intrusive and decentralized sexuality from the other. This sexuality that is in the enigmatic sexual messages of the adult will eventually be translated by the child. We therefore propose that the identification is one of the possible translation of these messages, which resituating the role of activity and passivity in the identification process. Using the Laplancheana's idea of myth as organizers of distress and, at the same time, repressed processes, let us to consider the identification process as well as repress process. Finally, we established a review on the identification of adults produced from the study of mass established by Freud.